Comparative analysis of energy dispatch strategies in PV-integrated renewable energy systems - Babaei, Reza; Ting, David S.-K.; Carriveau, Rupp (Next Energy, 2025)
The growing global population and escalating energy demands have highlighted the urgent need for a transition to sustainable and renewable energy sources. This study investigates the design and optimization of hybrid energy systems (HES) for Pelee Island, Canada—a remote community facing unreliable single-phase grid supply and increasing seasonal demand. The proposed HES integrates photovoltaic (PV) systems with tracking technologies, a biogas gasifier, diesel generator, lithium-ion battery storage, and grid interaction, under 2 dispatch strategies: Load Following (LF) and Cycle Charging (CC). Among 8 configurations, the CC-based system with VCA tracking (776 kW PV, 73 batteries) performs best, achieving a Net Present Cost (NPC) of $1.6 M, Cost of Electricity (COE) of $0.083/kWh, and Renewable Fraction (RF) of 78.7%. It meets 1,537,217 kWh of a 1,537,271 kWh annual load, with only 54.3 kWh unmet. The LF-VCA system offers the highest RF at 86.3% and the lowest emissions at 21.6 t/year but at a higher NPC of $1.62 M. Battery state of charge (SOC) stays above 60% in summer and often drops below 30% in winter. A 50% increase in SOCmin raises NPC by 20%, and a 1.5× capital cost nearly doubles COE. A 60% albedo boosts RF by 7.6% and reduces NPC by 18%. Compared to LF, the optimal CC system lowers NPC by $0.02 M and COE by $0.002/kWh, while producing 90,551 kWh/year of surplus energy. Grid imports peak in winter (>100 kW) and fall near zero in summer, while surplus exports exceed 200 kW during peak solar hours, enhancing system revenue through $0.15/kWh sales. •Hybrid energy system with a VCA tracker achieves $0.083/kWh COE and 78.7% RF.•SOCmin variations significantly impact NPC and COE in tracker-based systems.•Albedo improvements enhance solar efficiency, reducing NPC and renewable fraction.•CC dispatch strategy outperforms LF in cost-effectiveness and system efficiency.